The Influence of Prior Hyperthyroidism on Euthyroid Graves' Ophthalmopathy - Termote, Karolien (Hindawi Publishing Corporation, 2014)
Background. To investigate the influence of previous exposure to elevated thyroid hormones in euthyroid Graves' ophthalmopathy. Design. Retrospective, observational case series in university setting Median follow-up of 1 year with ranges of 0,8–7,6 years. Study performance of 10 years. Participants. We reviewed the clinical records of 731 Graves' ophthalmopathy patients. There were 88 (12%) patients with onset of Graves' ophthalmopathy during euthyroidism: 37 (5%) patients had ophthalmopathy without known history of thyroid dysfunction (group A) and 51 patients (6%) had onset of ophthalmopathy 6 months or more euthyroid after completion of antithyroid therapy (group B). Main Outcome Measures. Graves' ophthalmopathy was graded using the EUGOGO severity criteria. Unilaterality was investigated. TSH receptor antibody and thyroid peroxidase antibody were measured as markers of Graves' disease. Results. Group A had more often a normal ocular motility (46%) and less proptosis (14 ± 4 mm) compared to group B (22%, 16 ± 4 mm) (P = 0.032 and 0.028, resp.). TSH receptor antibody was more frequently elevated in group B (94%) than in group A (17%) (P < 0.001). Conclusion. Patients with euthyroid Graves' ophthalmopathy present more often with ocular muscle restriction and proptosis when previously exposed to elevated thyroid hormones.